Contemporary Management - Jones,Gareth R.; George, Jennifer M. (New York, N.Y. : McGraw-Hill Education, 2018)
Provide students with an account of the changes taking place in the world of business management. It shows the changes taking place in management practices by incorporating recent developments in management theory, research, and by providing vivid, current examples of how managers of companies large and more.
Part One: ManagementChapter 1: Managers and ManagingChapter 2: The Evolution of ManagementChapter 3: Values, Attitudes, Emotions, and Culture: The Manager as a PersonPart Two: The Environment of ManagementChapter 4: Ethics and Social ResponsibilityChapter 5: Managing Diverse Employees in a Multicultural EnvironmentChapter 6: Managing in the Global EnvironmentPart Three: Decision Making, Planning and StrategyChapter 7: Decision Making, Learning, Creativity, and EntrepreneurshipChapter 8: The Manager as a Planner and a Strategist Chapter 9: Value Chain Management: Functional Strategies for Competitive AdvantagePart Four: Organizing and ControllingChapter 10: Managing Organizational Structure and CultureChapter 11: Organizational Control and ChangeChapter 12: Human Resource ManagementPart Five: Leading Individuals and GroupsChapter 13: Motivation Performance Chapter 14: LeadershipChapter 15: Effective Groups and TeamsPart Six: Managing Critical Organizational ProcessesChapter 16: Promoting Effective CommunicationChapter 17: Managing Conflict, Politics, and NegotiationChapter 18: Used Advanced Information Technology to Increase Performance
Includes index
BBS
Trim Education
Keywords: Management; Business & finance